Hot topics in reactive oxygen therapy: Antimicrobial and immunological mechanisms, safety and clinical applications. (March 2017) - Dryden, Matthew; Cooke, Jonathan; Salib, Rami; Holding, Rebecca; Pender, Sylvia L.F.; Brooks, Jill
Highlights: Reactive oxygen species (ROS) delivered by engineered honey or gel. Novel antimicrobial with activity against all bacteria as well as fungal and viral activity. Topical treatment with antibiofilm activity. Huge therapeutic implications not just for wound healing but possibly mucosal infection in respiratory and urinary tract. Topical and local application, but could be applied to internal mucosal structures. Abstract: Reactive oxygen species (ROS), when combined with various delivery mechanisms, has the potential to become a powerful novel therapeutic agent against difficult-to-treat infections, especially those involving biofilm. It is important in the context of the global antibiotic resistance crisis. ROS is rapidly active in vitro against all Gram-positive and Gram-negative bacteria tested. ROS also has antifungal and antiviral properties. ROS prevents the formation of biofilms caused by a range of bacterial species in wounds and respiratory epithelium. ROS has been successfully used in infection prevention, eradication of multiresistant organisms, prevention of surgical site infection, and intravascular line care. This antimicrobial mechanism has great potential for the control of bioburden and biofilm at many sites, thus providing an alternative to systemic antibiotics on epithelial/mucosal surfaces, for wound and cavity infection, chronic respiratory infections and possibly recurrent urinary infections as well as local delivery to deeper structures and prosthetic devices. Its simplicity and stability lend itself to use in developing economies as well.